+0  
 
0
303
1
avatar+314 

How do you do this:

x^-3/2

ISmellGood  Sep 13, 2017
 #1
avatar+93866 
+1

How do you do this:

x^-3/2

 

\(\frac{x^{-3}}{2}=\frac{1*x^{-3}}{2}=\frac{1}{2x^{+3}}=\frac{1}{2x^{3}}\\~\\ \text{or maybe you mean}\\~\\ x^{-3/2}=1*x^{-3/2}=\frac{1}{x^{+3/2}}=\frac{1}{x^{3/2}}\\~\\ \text{can also be written as}\\ \frac{1}{x^{3/2}}=\frac{1}{(\sqrt x)^3}=\frac{1}{\sqrt{x^3}}\)

Melody  Sep 14, 2017

12 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.